ANALISIS PELAKSANAAN PROGRAM KESELAMATAN PASIEN PUSKESMAS MANGKANG, KOTA SEMARANG - Kholifatun Islami; Septo Pawelas Arso; Daru Lestyanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The issue about patient safety is one of important issues in health service. The implementation of patient safety is a must for all health services. The community health center as the institution which provides primary health services and makes the first contact to the individual, family, and the community, have to emphasize patient safety. “Seven Steps to Patient Safety” is a guide to the community health center to implement the patient safety program. The objective of this study id to analyze the implementation of patient safety in Mangkang Community Health Center. This is a qualitative research with dedscriptive approach. The data collection technique is through an interview and observation. The main informants are six staffs of each clinical units in Mangkang Community Health Center who know about the implementation of patient safety. The result of this study shows the implementation of patient safety in Mangkang Community Health Centre has not been optimized. The duty of PMKP team is not clear; there is no initiator of patient safety in each of clinical units; the implementation of patient safety is still in the step of collecting data; the lack of awareness in the importance of patient safety; the lack of staffs commitment in building the implementation of patient safety; there is no policy regarding the open communication with patient and their family; and the implementation of RCA which is not appropriate with the procedure. The suggestions given by the researcher are pointing the initiator of patient safety in each of clinical units; making policy/guides/SOP regarding the main tasks and functions of PMKP team; making policy regarding the open communication with patient and family; and increasing the commitment in building the implementation of patient safety.